Correlation Between Interest With Participation of Toddlers Mothers in the Activities of the Posyandu - Dafid Efendi; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low participation of mothers under five to come to the posyandu, presumably because mothers of toddlers were less interested in the activities of the Bunga Tanjung Gasan Gadang Posyandu, Padang Pariaman Regency. This study aims to see a description of the interests of mothers of children under five, to see the description of the participation of mothers of children under five, and to see the relationship between interest and the participation of mothers of children under five. This type of research is quantitative with a correlational approach. The population of this study were all parents/participants in the posyandu as many as 29 people. While the sample was taken using a purposive technique as much as 75% of the population of 21 people. Data collection techniques using a questionnaire. Meanwhile, for the data analysis technique, the percentage formula and the rho sperm formula were used. The results of this study indicate that a) the interest of mothers of children under five in posyandu activities is still low; b) the participation of mothers under five in posyandu activities is still low; and c) there is a significant relationship between interest and participation of mothers under five in posyandu activities. It is recommended to posyandu cadres to carry out various creativity that can develop the interest of mothers of toddlers so that they participate in participating in every activity in posyandu and mothers of toddlers to participate in posyandu activities.